Insecticidal and repellent activities of essential oils from Aloysia Citriodora and Minthostachys Verticillata against Sitophilus Zeamais (Coleoptera: Curculionidae) - Arena, J. S. (2018)
Fil: Arena, J. S. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Biología Vegetal; Argentina.